The game is an active way to learn German. Active methods of teaching German Active methods of teaching in German language classes - Adxamjonov Muhammadali (Genius Journals, 2022)
It is necessary to switch to innovative methods of teaching. My students are with me. Each person needs certain thinking skills and personal qualities: analysis, comparison, distinguishing the main thing, ability to solve problems, ability to improve oneself and self-esteem, responsible, independent the ability to be, create and create. cooperation is what a child needs to enter this world. And as a teacher, my main business is that there is no coercion, every student has the opportunity to find his place, to show initiative and independence, to freely realize his abilities and educational needs is to create an emotionally comfortable, stimulating and creative environment.
Keywords: comfortable; freely; abilities; create